Indigenous Art Forms in the Akuapem North Basic Schools’ Cultural Festival - Isaac Horsu; Eric Kwamina Ansa (Professorline, 2026)
Performing drama has increasingly emerged as a critical cultural practice in contemporary society, functioning not merely as artistic expression but as a space where identity, culture, and power are actively negotiated. This perspective article reflects on performing drama as a socio-cultural arena in which dominant narratives are questioned, marginalized voices are articulated, and collective meanings are reconfigured. Rather than presenting empirical findings, this article offers a conceptual reflection grounded in contemporary art and cultural studies. It argues that performing drama operates as a dynamic site of negotiation between tradition and modernity, local and global cultures, and authority and resistance. By situating drama within broader social and political contexts, this article highlights its potential role in fostering critical awareness and cultural agency in contemporary society.